(untitled) (Global Journals of Research in Engineering, 2023)
This paper offers a holistic approach in reducing energy consumption in industrial facilities specifically warehouse logistics facilities by exploring various ways or methods companies can adopt to reduce their warehouse logistics facilities energy consumption environmental impact and operational expenses It highlights the importance of why companies should invest in these green initiatives as it will assist companies in complying with increasing regulations and mandates regarding greenhouse gas emissions GHG fulfilling their social responsibility to increasingly environmentally conscious consumers rising utilization of e-commerce and rising populations The demand for these facilities will increase and companies must be ready to meet this demand carefully to balance their social responsibilities by reducing their GHGs and their commitments to their shareholders by maintaining or improving their profit margins Throughout this paper measures for existing or in operation warehouse logistics facilities will be highlighted and then the paper will propose measures for future warehouse logistics facilities to be considered to minimize their environmental impact This paper aims to provide measures for companies to reduce their warehouse logistics facilities GHGs specifically their energy consumption and for their existing warehouse logistics facilities and future ones